The immediate effects of iTBS on the muscle activation pattern under challenging balance conditions in the patients with chronic low back pain: A preliminary study - Yang, Jiajia; Fu, Ruochen; Hao, Zengming; Lin, Nanhe; Cheng, Xue; Ma, Jinjin; Zhang, Yushu; Li, Yan; Lo, Wai Leung Ambrose; Yu, Qiuhua; Wang, Chuhuai (Frontiers in Neuroscience, 2023)
Background: The patients with chronic low back pain (CLBP) showed impaired postural control, especially in challenging postural task. The dorsolateral prefrontal cortex (DLPFC) is reported to involve in the complex balance task, which required considerable attentional control. The effect of intermittent theta burst stimulation (iTBS) over the DLPFC to the capacity of postural control of CLBP patients is still unknown. Methods: Participants diagnosed with CLBP received a single-session iTBS over the left DLPFC. All the participants completed the postural control tasks of single-leg (left/right) standing before and after iTBS. The activation changes of the DLPFC and M1 before and after iTBS were recorded by functional near-infrared spectroscopy (fNIRS). The activation pattern of the trunk [transversus abdominis (TrA), superficial lumbar multifidus (SLM)]) and leg [tibialis anterior (TA), gastrocnemius medialis (GM)] muscles including root mean square (RMS) and co-contraction index (CCI) during single-leg standing were measured by surface electromyography (sEMG) before and after the intervention. The paired t-test was used to test the difference before and after iTBS. Pearson correlation analyses were performed to test the relationship between the oxyhemoglobin concentration and sEMG outcome variables (RMS and CCI). Results: Overall, 20 participants were recruited. In the right-leg standing condition, compared with before iTBS, the CCI of the right TrA/SLM was significantly decreased (t=-2.172, p=0.043), and the RMS of the right GM was significantly increased (t=4.024, p=0.001) after iTBS. The activation of the left DLPFC (t=2.783, p=0.012) and left M1 (t=2.752, p=0.013) were significantly decreased and the relationship between the left DLPFC and M1 was significant after iTBS (r=0.575, p=0.014). Correlation analysis showed the hemoglobin concentration of M1 was negatively correlated with the RMS of the right GM (r=-0.659, p=0.03) and positively correlated between CCI of the right TrA/SLM (r=0.503, p=0.047) after iTBS. There was no significant difference in the brain or muscle activation change in the left leg-standing condition between before and after iTBS. Conclusion: iTBS over the left DLPFC seems to be able to improve the muscle activation pattern during postural control ability in challenging postural task, which would provide a new approach to the treatment of CLBP.